Students’ Perception on the Use of Audio Visual Materials in Learning English at Senior High School - Redha Shafira; Nur Rosita (Universitas Negeri Padang, 2022)
This research aims to analyze students’ perception on the use of audio visual materials in learning English seen from four language skills, and analyzed from the attractiveness, effectiveness, relevance, and motivation. The questionnaire and interview were used as the instrumentation of this research. This research was conducted at the 11th grade of students in the science program of SMAN 3 Bukittinggi academic year 2022/2023. The researcher used cluster random sampling to choose the sample. Two classes in total 63 students were taken as the sample of this research. In this study, descriptive research with quantitative and qualitative methods was used to analyze the data. Based on the data from the questionnaire and interview, students have positive perceptions on the use audio visual material in learning English seen from four language skills; listening, speaking, reading, and writing. It is shown by the result of the interview and the total mean of the questionnaire.